Partial-immuned mice as carriers for haemorrhagic septicaemia - A possibility? - Asrol Sany Hj Arshad (2005.)
This study was conducted to determine the carrier status in partial-immuned nice for Haemorrahgic Septicaema. Forty male Swiss Albino mice aged between six and eight weeks were divided into two groups: control and trial. Mice from the trial group were vaccinated with alum precipitate vaccine, 0.5 ml subcutaneously, while the control group was untreated. The study was conducted within 28 days. Every seven days, five mice from the tria; group and two from the control group will be challenged with pathogenic Pasteurella multocida type 6:B Carter strain C82. Post-mortem will be carried out on dead mice and mice that survived will be kept alive for a week before sacrificed. Pool organs will be collected for bacterial culture and blood from the heart was taken for thin smear to detect the bipolar organism, Pasteurella multocida. Blood will be collected before and after challenge to detect the antibody level using ELISA technique. From the study all mice from the control group did within 24 to 48 hours post-challenge while mice from the trial group have shown variable results where 10 out of 40 mice died. Mice that survived showed negative results for carrier's status for Haemorrhagic Septicaemia. As a conclusion, partial-immuned mice cannot become carriers for Haemorrhagic Septicaemia.
Project paper (D.V.M.) - Universiti Putra Malaysia, 2005.